(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of cognitive impairment and analyze associated factors among menopausal women in Son Tra regional, Da Nang city in 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 393 menopausal women aged 45-60 years. Data were collected through face-to-face interviews using a structured questionnaire. Cognitive impairment was assessed using the MMSE. Data were analyzed using SPSS 16.0, and Chi-square test was applied with a significance level of p < 0.05. Results: The prevalence of cognitive impairment was 14.2%. Factors significantly associated with cognitive impairment included chronic diseases (28.2% vs. 8.3%; p < 0.001), smoking (24.2% vs. 12.4%; p = 0.015), and periodic health check-ups (18.6% vs. 9.0%; p = 0.007). No statistically significant associations were found with age, religion, nutritional status, age at menarche, age at menopause, and physical activity. Conclusion: The prevalence of cognitive impairment among menopausal women in Son Tra was relatively low. Control of chronic diseases and modification of lifestyle behaviors play important roles in the prevention of cognitive impairment.